(untitled) (Research, Society and Development, 2022)
The presence of a nurse in school environments brings continuous improvements in health education processes, provides a better quality in child health care, as well as a sense of security for other professionals working in these units. However, even with the enactment of Law No. 1,616 of 2011, which requires the presence of the professional nurse in school environments, the performance of this professional in this environment is scarce. To investigate the presence of nurses in public schools and day care centers in the rural area of ​​Imperatriz -MA. Documentary, descriptive research with a quantitative approach carried out in the rural area of ​​the municipality of Imperatriz - MA. For data collection. A consultation was carried out at the Municipal Secretary of Education (SEMED) of the municipality of Imperatriz. Collection of information related to the total number of municipal schools and day care centers, address, area, village, number of students and the presence of the professional nurse at the school or day care center. The municipality of Imperatriz has 127 municipal school units. Of these 100 are located in urban areas and 27 in rural areas. The school units in the rural area include a total of 2646 students. It was observed that no school unit has the presence of a nursing professional in the school. It brings a reflection on the importance of the role of the nurse professional in these spaces.